2018
DOI: 10.1016/j.trre.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Preserving and perfusing the allograft pancreas: Past, present, and future

Abstract: The concept of organ preservation by perfusion dates back to the mid-19th century. Innovations since then have included temperature regulation, perfusion fluid composition and various pumping systems. Advances made in liver, heart and kidney machine preservation are now contributing to increased graft utilisation, assessment of graft viability and potentially improved graft survival. Pancreas transplantation has not benefitted to the same extent from the application of perfusion technology, although the need i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…These act mostly by reducing cellular swelling and maintaining pH balance and in some solutions oxygen-free-radical scavengers and precursors for ATP are added. Studies have shown that preservation with either UW, Histidine-Tryptophan-Ketoglutarate (HTK), Celsior and Institute Georgez Lopez-1 (IGL-1) did not show superiority over another [37]. Currently, no studies have been performed that analyzed the effect of different preservation solutions on DCD pancreas transplants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These act mostly by reducing cellular swelling and maintaining pH balance and in some solutions oxygen-free-radical scavengers and precursors for ATP are added. Studies have shown that preservation with either UW, Histidine-Tryptophan-Ketoglutarate (HTK), Celsior and Institute Georgez Lopez-1 (IGL-1) did not show superiority over another [37]. Currently, no studies have been performed that analyzed the effect of different preservation solutions on DCD pancreas transplants.…”
Section: Introductionmentioning
confidence: 99%
“…The organ is placed in the solution which is presaturated with oxygen or continuously oxygenated during preservation. Oxygen is delivered to the pancreas by passive diffusion, with the intention to achieve ATP production in the presence of precursors in the preservation solution [36, 37]. Experimental studies in small animals showed promising results of TLM regarding to ATP levels when compared with SCS [38].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the large number of perfusion systems and preclinical and clinical trials, we exemplarily discuss the potential of machine perfusion in the setting of liver perfusion in the following section. Various reviews and reports on perfusion systems for the heart , lung , kidney , and initial studies in pancreas and VCA are available elsewhere.…”
Section: Advances In Organ and Tissue Preservationmentioning
confidence: 99%
“…This technology will also be able to be leveraged toward solving other challenges. There is a shortage of donor supplied organs other than the heart as well—kidneys, livers, lungs, and more (Dholakia et al, ; Hou, Sui, Che, Chen, & Dai, ; Orens & Garrity, ; Scheuher, ), each of which could ultimately be created through this process. The good news is that the 3D bioprinting process has the potential to create a wealth of organs in addition to hearts, and thus the potential to save even more lives.…”
Section: Challenges Remainmentioning
confidence: 99%